(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
1- It is the first time that extensive news on the subject is provided, with detailed information on Galicia, but also including important data from Northern Portugal, León and Asturias. 2- An important comparative analysis of Galician texts is carried out, some, such as Mouruás, or Mouriscados, unpublished until now, discovering their kinships with representations of Cuenca, Teruel and Valencia, or highlighting a phenomenon of diffusion from those lands of Levante to the northwest. 3- Although in the representations the theme of the Reconquest is touched, in the work it is clear that there are two other themes present in the staging: the Carolingian epic, with backgrounds such as the "Pseudo-Turpin" (present in the "Codex Calixtinus "), compostelana work of the twelfth century, and the" History of Emperor Charlemagne and the Twelve Peers of France ", and also the Turkish-Berber Corsican and the problem of Christian captives. 4- Another aspect to be noted is that of the successive updates of the original theme, giving rise to: a) the incorporation of literary texts to the works, and b) the updating of the antagonists, coming to incorporate figures of the African war of 1859-60 or French wars of the late eighteenth and early nineteenth centuries. 5- The work ends with some considerations about the socio-cultural re-significance of the representations in the present, when they function as referents for the loical identity or as ingraders of natives of the place they emigrated